Combined application of electrolysed water and ultrasound to improve the sanitation of knives in the meat industry. (24th July 2019) - Brasil, Carla C. B.; de Menezes, Cristiano R.; Jacob‐Lopes, Eduardo; Barin, Juliano Smanioto; Zepka, Leila Queiroz; Campagnol, Paulo Cezar Bastianello; Wagner, Roger; Cichoski, Alexandre José
Summary: This study investigated the effect of the combination of basic electrolysed water (BEW) and slightly acid electrolysed water (SAEW) with ultrasound (US) for cleaning and sanitation of the knives used in slaughtering processes. The knives were sonicated in a US bath using two modes of operation (normal and sweep) in two steps: (i) 5 min with BEW and (ii) 10 min with SAEW at 35 °C. The microbiological counts and the possible changes in the physical structure of the knives were evaluated. The association BEW + SAEW + US, in the sweep mode, provided lower mesophilic, enterobacterial, Staphylococcus aureus and yeast counts when compared to the values recommended by the international legislation. In addition, these conditions removed all organic residues from the knife blades and promoted the highest migration rate of the residues to the US water bath (12.35 mg/L·min), without modifications in the knife blades. Thus, cleaning and sanitation of knives was feasible with the association of BEW + SAEW + US, which could be a useful alternative for the meat industry. Abstract : Emerging technologies in the meat industry.